Political Caricature to Mobilize Solidarity Through Humor (Alternautas, 2024)
As part of our special issue, we invited artist Pedro X. Molina to choose a selection of his works to dialogue with our central themes of past and present European-Latin American solidarities, and the role of artifacts therein. Molina has chosen three caricatures for our special issue, which we include over the coming pages. Reflecting on current socio-political affairs such as Nicaraguan authoritarianism, migration to the US, and memories of violence, his work manages to address these issues with sharpness and rigour.